A community based cross-sectional study: perception of adults about corona virus disease (COVID-19) in North India - Verma, Ramesh; Chayal, Vinod; Kalhan, Meenakshi; Bhalla, Kapil; Dhaka, Rohit; Agrawal, Ginni; Kumar, Gopal; Sachdewa, Aman (International Journal Of Community Medicine And Public Health, 2021)
Background: Coronavirus disease (COVID-19) is caused by a novel virus SARS Coronavirus- 2 (SARS-CoV-2). First case of this infection was reported in December 2019 in Wuhan city of China and after that it spread globally. WHO declared it as a pandemic when the infection was reported from all six WHO regions. Methods: The study was community based cross-sectional designed and was carried out in an urban slum of Rohtak before the first lockdown was announced in India. The study recruited 400 adults of age 18-50 years. Results: In the study, 90% of subjects had heard of corona virus infection and majority of source of information was television and peer group. The association between socio-demographic characteristics like literacy and caste with knowledge about corona virus infection was found statistically highly significant but this association in gender and age was not found no statistically significant. Conclusions: The study concluded that majority of subjects had heard about COVID-19 and majority knew the correct mode of transmission. Most of the study subjects knew that wearing face mask and frequently hand washing are the only preventive measures available against COVID-19.